Surveillance capitalism in coastal governance: Datafication, digital control, and fishermen’s precarity in Madura, Indonesia - Edy Purwanto; Zainal Abidin; Indra Jaya Kusuma Wardhana; Sittiy Muizze; Margaretha Diah Ayu (C-DISC, 2026)
The digitalization of fisheries governance in Indonesia has increasingly transformed coastal communities into data-driven administrative subjects. This study examines how the logic of surveillance capitalism operates within the fisheries governance system at UPT PPP Pasongsongan, Sumenep, East Java. Employing a qualitative phenomenological approach informed by Shoshana Zuboff’s theory of surveillance capitalism, the research investigates how digital infrastructures—including the KUSUKA application, the Si-Kapal vessel monitoring system, GPS tracking, WhatsApp communication groups, and integrated fisheries databases—reconfigure the relationships among the state, governing institutions, and small-scale fishermen. Data were collected through in-depth interviews, field observations, and institutional document analysis involving government officials and local fishing communities. The findings demonstrate that digitalization extends beyond administrative modernization, generating new forms of surveillance, data extraction, and dependency among fishermen. Through continuous monitoring and platform-based coordination, fishermen are increasingly positioned as data subjects within bureaucratic governance systems. Furthermore, fragmented authority between provincial and district governments creates governance gaps that intensify fishermen’s vulnerability amid climate uncertainty and economic precarity. This study argues that surveillance capitalism in coastal governance is manifested not only through large-scale corporate digital platforms but also through routine bureaucratic digitalization practices that transform fishermen’s everyday livelihoods into governable data infrastructures.